Antibacterial activity of a berberine nanoformulation - Nguyen, Hue Thi; Pham, Tuyet Nhung; Le, Anh-Tuan; Thuy, Nguyen Thanh; Huy, Tran Quang; Nguyen, Thuy Thi Thu (Beilstein Journal of Nanotechnology, 2022)
This study describes the preparation of berberine (BBR) in nanoformulation to enhance its solubility and increase its antibacterial effectiveness against hospital-acquired infections. BBR nanoparticles (BBR NPs) were formed by antisolvent precipitation (ASP) using glycerol as a safe organic solvent. UV–vis absorption spectra demonstrated that the solubility of BBR NPs was greatly enhanced compared to that of pure BBR. Glycerol played a role as a stabilizer for BBR NPs through the formation of hydrogen bonds between glycerol and BBR NPs. The prepared BBR NPs have a narrow size distribution with an average diameter of 156 nm at a concentration of 2.0 mg/mL, measured by dynamic light scattering. After nanoformulation, the concentration of BBR NPs could reach up to 5.0 mg/mL, which is much higher than the saturation concentration without treatment. Results show a strongly enhanced antibacterial activity of BBR NPs compared with that of pure BBR at the same concentration. The minimum bactericidal concentration of BBR NPs against methicillin-resistant Staphylococcus aureus and Escherichia coli O157:H7 was found to be 2.0 and 5.0 mg/mL, respectively. Transmission electron microscopy showed that BBR NPs surrounded the bacterial cells and severely damaged the cell walls. Therefore, BBR NPs prepared by ASP appear to be a potential candidate for the treatment of bacterial pathogens.
Keywords: antibacterial activity; antisolvent precipitation (ASP); berberine nanoparticles (BBR NPs); glycerol; solubility